Association between COMMD1 gene polymorphism rs11125908 and rheumatoid arthritis in the Cuban population - M. Carpio Alvarez; A. Cintado Benitez; T. Diaz Argudin; H. Nodarse Cuni; M.d.C Dominguez Horta; J.R. Fernández Massó (PAGEPress Publications, 2024)
Objective. To evaluate the association of the rs11125908 polymorphism in the COMMD1 gene in the Cuban population with rheumatoid arthritis (RA). Methods. In this case-control study, 161 RA patients and 150 control subjects were genotyped for rs11125908 by the allele-specific polymerase chain reaction method. DNA sequencing was used to verify the assignation of the polymorphism. The odds ratios (OR) and their 95% confidence interval were calculated by logistic regression to determine the associations between genotypes and RA using the SNPStats software. Results. An association of the single nucleotide polymorphism with the disease was found in the overdominant model (p=0.025; OR=1.91) for the AG genotype. Our analyses revealed an association between rs11125908 and the subgroup of patients with swollen joints < median under the codominant model for AG (p=0.034; OR=2.30) and GG genotype (p=0.034; OR=0.82) and with the overdominant model (p=0.01; OR=2.38). The subgroup of patients with an age of onset lower than the mean and AG genotype showed an association in the overdominant model (p=0.027; OR=2.27). Disease activity score 28 with erythrocyte sedimentation rate and disease duration variables were not associated with the rs11125908 polymorphism. Conclusions. rs11125908 was associated with RA and with the number of swollen joints and age of onset subgroup analyses. We provide concepts for treatments for RA, based on pharmacological management of COMMD1 expression.